The Usefulness of Information Contained in Financial Statements - Marek CIESLAK (Communications of International Proceedings, 2024)
The paper delves into the efficacy of financial statements, scrutinizing the quality determinants and the role of fair value in financial reporting. It argues that while accounting standards aim to enhance the quality of financial statements for better capital market decisions, the real challenge lies in balancing the usefulness and reliability of the information provided. The conclusion suggests a potential solution: allowing entities to choose between historical cost and fair value for financial reporting, which could lead to industry-specific practices that optimize the trade-off between information utility and reliability. This choice could foster a competitive environment where the most effective valuation method prevails, ultimately benefiting the transparency and functionality of financial statements.
Keywords: Financial statements; information usefulness; fair value; accounting regulations